Low Doses of Sucralose Alter Fecal Microbiota in High-Fat Diet-Induced Obese Rats - Zhang, Minchun; Chen, Jie; Yang, Minglan; Qian, Cheng; Liu, Yu; Qi, Yicheng; Feng, Rilu; Yang, Mei; Liu, Wei; Ma, Jing (Frontiers in Nutrition, 2021)
Introduction: Artificial sweeteners (AS) are widely used as sugar substitutes to reduce calorie intake. However, high doses of AS induced glucose tolerance by modulating gut microbiota. The objective of this study was to investigate the effects of lower doses of sucralose on fecal microbiota in obesity. Materials and methods: Eight weeks after high-fat diet, the male Sprague Dawley rats were randomly divided into four groups (n=24) and administrated by a daily gavage of 2ml normal saline (CON), 0.54mM sucralose (N054), 0.78mM sucralose (N078) and 324mM sucrose (S324) respectively. After four weeks, fecal samples were obtained and used in 16S ribosomal RNA gene sequencing. The richness and diversity of fecal microbiota did not change by these sucralose and sucrose dosage. Both 0.54mM (0.43mg) and 0.78mM (0.62mg) tended to reduce the beneficial bacteria, Lactobacillaceae and Akkermansiaceae. The relative abundance of family Acidaminoccaceae and its genus Phascolarctobacteriam were increased with 0.54mM sucralose. In functional prediction, 0.54mM sucralose increased profiles of carbohydrate metabolism, whereas 0.78 mM sucralose enhanced that of amino acids metabolism. Discussion and conclusion: The lower doses of sucralose altered the compositions and the metabolic functions of fecal microbiota. The benefits of sucralose and its recommended dose for obese patients should be reassessed comprehensively.